Students’ Mathematical Literacy: Systematic Literature Review (SLR) - Ahbi Mahdianing Rum; Dadang Juandi (Hipotenusa : Journal of Mathematical Society, 2022)
The aim of this study was to describe the research results related to students’ mathematical literacy analyzed based on their learning style or cognitive style. The method used in this study was Systematic Literature Review (SLR). The sample was 27 articles consisting of 18 and 19 articles about students’ mathematical literacy based on: learning style and cognitive style, respectively. The samples were articles indexed in SINTA, published in 2018 until September 2022 and located in Indonesia. The description in this study will be reviewed based on the journal indexes, year of publication, methods used, level of education, number of subjects, research locations, and the theory used both in the learning style and cognitive style. Through the SLR method, it was found the articles were dominantly published in SINTA 4, there were a decreasing and increasing in number of articles published in SINTA, qualitative method was dominant followed by mix method and quantitative method, the research conducted in junior high school was dominant, 18 out of 27 researches used more than 30 subjects, the research was dominantly conducted in Java, De Porter Hernacki theory and Witkin Goodenough were dominantly utilized in learning style and cognitive style research, respectively.